Estrategia didáctica y su incidencia en el desarrollo del lenguaje oral en niños/as de 3 a 5 años de la unidad educativa “Juan León Mera”, cantón Montalvo, provincia de los Ríos. - Almeida Ponce, Sara Maria (2016)
Teaching strategies considered in the world as activities used by teachers in different institutions to the development of the process of teaching and student learning possible, as the concept of learning to learn is always the human being, since you need to the teacher knows the mental makeup of his students why developed countries that conduct research seeking to develop teaching strategies that encourage and develop the different processes of school learning and provide benefits in children rapidly increasing vocabulary, teachers of educational Unit Juan Leon Mera are challenged to use teaching strategies in their daily teaching practice, and thus ensure the proper conduct of its work, thus achieving meaningful learning with students, with the main objective to analyze the impact of the strategy teaching in oral language development in children / as 3 to 5 years of the Educational Unit "Juan Leon Mera" canton Montalvo, Los Rios province. That is why the following research is performed, framed mista going to be a possible solution and teaching strategy in the development of oral language in children / as